Attentional limitations in processing sequentially presented vibrotactile targets. - Hillstrom, A; Shapiro, K; Spence, C (2002)
In seven experiments, participants experienced rapid, serially presented streams of vibrations and responded to specific targets in the streams. In visual (and sometimes auditory) streams presented in this manner, it is typical to find a deficit in reporting the second of two targets when both must be reported and the second appears within a short temporal interval of the first, but not when identical displays are presented but only the second target must be reported (e.g., the attentional blink, or AB). This conventional AB pattern was found in the last experiment, in which judgments were about target location. However in the first six experiments reported here, in which judgments were about frequency, intensity, duration, or location of targets, accuracy was dependent on target separation regardless of whether or not the first target was reported. This unconventional pattern could represent an AB if the first target was attended even when it was not reported. The evidence for this claim and an alternative possibility that location judgments are especially sensitive to attention manipulations are discussed.